Effects of nutrient content claims, sports celebrity endorsements and premium offers on pre‐adolescent children's food preferences: experimental research. Issue 2 (29th April 2013) - Dixon, H.; Scully, M.; Niven, P.; Kelly, B.; Chapman, K.; Donovan, R.; Martin, J.; Baur, L. A.; Crawford, D.; Wakefield, M.
Summary What is already known about this subject Food marketing has come under scrutiny for its likely contribution to promoting unhealthy eating and obesity in children. There is limited published evidence regarding the effects of food packaging promotions on children. Nutrient content claims and sports celebrity endorsements on food packs influence adults to prefer energy‐dense and nutrient‐poor (EDNP) products bearing such promotions, especially among the majority who do not read the nutrition information panel. What this study adds This study experimentally tested pre‐adolescent children's responses to three common food marketing techniques: nutrient content claims, sports celebrity endorsements and premium offers. On‐pack nutrient content claims made pre‐adolescents more likely to choose EDNP products and increased perceptions of their nutrient content. Sports celebrity endorsements made pre‐adolescent boys more likely to choose EDNP products. Objectives To assess pre‐adolescent children's responses to common child‐oriented front‐of‐pack food promotions. Methods Between‐subjects, web‐based experiment with four front‐of‐pack promotion conditions on energy‐dense and nutrient‐poor (EDNP) foods: no promotion [control]; nutrient content claims; sports celebrity endorsements (male athletes) and premium offers. Participants were 1302 grade 5 and 6 children (mean age 11 years) from Melbourne, Australia. Participants chose their preferred product from a randomly assigned EDNP food pack and comparable healthier food pack then completed detailed product ratings. Child‐oriented pack designs with colourful, cartooned graphics, fonts and promotions were used. Results Compared to the control condition, children were more likely to choose EDNP products featuring nutrient content claims (both genders) and sports celebrity endorsements (boys only). Perceptions of nutritional content were enhanced by nutrient content claims. Effects of promotions on some product ratings (but not choice) were negated when children referred to the nutrition information panel. Premium offers did not enhance children's product ratings or choice. Conclusions Nutrient content claims and sports celebrity endorsements influence pre‐adolescent children's preferences towards EDNP food products displaying them. Policy interventions to reduce the impact of unhealthy food marketing to children should limit the use of these promotions.